Optimalisasi Pemanfaatan Sampah Batok Kelapa sebagai Bahan Dasar Pembuatan Bahan Pengawet Alami - Andi Asyhari; Istia Nur Hayati; Putri Linda Riani (Jurnal Pro-Life, 2022)
Most food products currently use formalin as a preservative, of course this is very dangerous for health. However, this problem can be solved by developing a liquid smoke pyrolysis process. The purpose of this study was to optimize the utilization of coconut shell waste as the basic material for making natural preservatives. The research method used in this research is Extended Storage Studies (ESS). The results of this study are the results of pyrolysis in the form of liquid smoke from coconut shells can be used as a natural preservative in fish. Because liquid smoke contains phenolic compounds and organic acids that can inhibit the growth of bacteria or microorganisms. This is evident in the immersion of fish using liquid smoke with concentrations of 20%, 40%, 60%, 80% and 100% which are soaked for 30 minutes. The research conducted was observing the texture, aroma, eyes, gills, weight, fish condition and fish pH. From the liquid smoke immersion, the fish's pH decreased every day from 6 to 3 and the fish did not grow microorganisms. In contrast to fish without treatment, the pH of the fish is increasing from 6 to 8 and the more microorganisms are growing day by day.